OC-035 Lifetouch®: A Novel Remote Monitoring Device To Identify Patients With Advanced Cirrhosis Most At Risk Of Decompensation – A Proof Of Concept Study. (9th June 2014) - Chatterjee, D; Jones, HE; León, AG; Privitera, G; Jalan, R; Mookerjee, RP
Abstract : Introduction: Hospital readmission from inter-current illness is common in advanced cirrhosis. Community monitoring of these patients with simple information-based technology may facilitate early problem recognition and intervention. Heart rate variability (HRV) has been deemed the 'gold standard' tool to characterise autonomic dysfunction, which is widely reported in cirrhosis, and remains independent of aetiology, and its severity has been shown to correlate with prognosis. However, the methods to study continuous measurement of HRV and studies in advanced cirrhosis are limited. Aims: This study used a wireless-monitoring technology, Lifetouch® system (Isansys), to assess changes of HRV remotely in acute-on-chronic liver failure (ACLF) patients, and evaluated the relationship to the severity of disease and inflammatory indices. Methods: Following ethical and local site approval, nineteen patients (13 male/6 female; mean age 52.5 ± 12.0 years) had HRV assessment following presentation to The Royal Free hospital, using the Lifetouch ® system, with the standard deviation of the R-R interval (SDNN) used to collect changes in HRV. This novel system enabled continuous, wireless evaluation of HRV, which was compared with clinical, biochemical and inflammatory indices (IL-6, IL-8 and IL-10 measured by multiplex cytokine analysis). Results: HRV, as determined by SDNN, was significantly greater in cirrhosis patients with Child-Pugh scores <10 compared to >10 (31.26 ± 14.90 vs. 10.80 ± 5.61 ms). Similarly, UKELD correlated inversely with SDNN (R 2 = -0.46; p < 0.01). Spearman's rank analysis of SDNN in relation to the inflammatory indices: WCC, CRP, IL-6, IL-8 and IL-10 levels were -0.60 (p = 0.01), -0.56 (p = 0.01), -0.77 (p = 0.02), -0.86 (p = 0.01) and -0.79 (p = 0.04), respectively. Using a SDNN cut-off of ≤20 ms to signify patients with advanced disease (Child C), all inflammatory indices were shown to be significantly increased (P < 0.01). Conclusion: This pilot study provides proof of concept that remote monitoring showing reduced HRV, identifies patients with increased inflammation, more advanced liver disease and those most likely to present with acute decompensation of cirrhosis. Further study and refinement of this system may facilitate community monitoring of advanced liver disease patients, to provide 'alarm' signals that highlight acute decompensation and precipitate early intervention care pathways. Disclosure of Interest: None Declared.